TEORI HUKUM PROGRESIF (Prof. Dr. Satjipto Rahardjo, S.H.) - Anisa Rizki Fadhila, Anisa Rizki Fadhila (SINDA: Comprehensive Journal of Islamic Social Studies, 2021)
Progressive law aims to lead people to a just, prosperous life and make people happy. This progressive legal research pays great attention to the role of human behavior, in this law it is diametrically opposed to the notion that law is only a matter of regulation. Progressive law refuses to maintain the status quo in law. Maintaining the status quo has the same effect as when people argue that law is the measure of all things, and people are for the law. Such way of law is in line with positivistic, normative and legalistic ways.